2009
DOI: 10.3808/jei.200900141
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Radiometric Behavior of LISS III Data of IRS 1D and IRS P6 for Landscape Ecological Application

Abstract: ABSTRACT. In the recent time, the usage of multi date satellite remote sensing data is a commonest practice to monitor and model the landscape dynamics. But the reliability of information obtained from such time series analysis of satellite imagery depends heavily on the coherence in the spectral behavior of the multi-dates satellite data. The inconsistency in the spectral behavior among the multidate satellite data may be attributed to differences in satellite orbit and sensor characteristics and even the env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…The satellite data used in this study were obtained from the sensors IRS-1D LISS III, Landsat-TM and Landsat-MSS. The LISS-III sensor of the Indian Remote Sensing satellite (IRS) has 4 bands with a spatial resolution of 23.5 m, Landsat-TM has 7 bands with a spatial resolution of 30 m and MSS has 4 bands with a spatial resolution of 80 m. Indian remote sensing satellites for the period 1999-2000 have been utilised in this research as IRS data have been successfully used for various ecological applications (Sharma, 2009). Other ancillary data used were: A hybrid classification scheme is adopted in this research for preparing the land cover map, in which a particular class is identified, isolated and extracted using the best possible procedure (either supervised or unsupervised), and finally the individual classes extracted were integrated.…”
Section: Database Creationmentioning
confidence: 99%
“…The satellite data used in this study were obtained from the sensors IRS-1D LISS III, Landsat-TM and Landsat-MSS. The LISS-III sensor of the Indian Remote Sensing satellite (IRS) has 4 bands with a spatial resolution of 23.5 m, Landsat-TM has 7 bands with a spatial resolution of 30 m and MSS has 4 bands with a spatial resolution of 80 m. Indian remote sensing satellites for the period 1999-2000 have been utilised in this research as IRS data have been successfully used for various ecological applications (Sharma, 2009). Other ancillary data used were: A hybrid classification scheme is adopted in this research for preparing the land cover map, in which a particular class is identified, isolated and extracted using the best possible procedure (either supervised or unsupervised), and finally the individual classes extracted were integrated.…”
Section: Database Creationmentioning
confidence: 99%